High-Resolution NMR of Folded Proteins in Hyperpolarized Physiological Solvents - Kadeřávek, Pavel; Ferrage, Fabien; Bodenhausen, Geoffrey; Kurzbach, Dennis (Chemistry (Weinheim an der Bergstrasse, Germany), 2018)
Hyperpolarized 2D exchange spectroscopy (HYPEX) to obtain high-resolution nuclear magnetic resonance (NMR) spectra of folded proteins under near-physiological conditions is reported. The technique is based on hyperpolarized water, which is prepared by dissolution dynamic nuclear polarization and mixed in situ in an NMR spectrometer with a protein in a physiological saline buffer at body temperature. Rapid exchange of labile protons with the hyperpolarized solvent, combined with cross-relaxation effects (NOEs), leads to boosted signal intensities for many amide 1 H-15 N correlations in the protein ubiquitin. As the introduction of hyperpolarization to the target protein is mediated via the solvent, the method is applicable to a broad spectrum of target molecules.
Keywords: hyperpolarized water; protein NMR spectroscopy; cross-relaxation effect; proton exchange; dissolution DNP